Socrates and his livelihood (Revista Archai, 2021)
Known for his poverty, what does Socrates live on? A careful study of the sources reveals that he could satisfy his needs in three different ways: by begging, by the generosity of his friends and by the gifts promised by powerful men. However, regarding these means, the sources are ambivalent: some indicate that Socrates used them, but others that he firmly rejected them in order to preserve his independence.